2012
DOI: 10.5539/jsd.v5n2p43
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Alleviation Efforts through a Community Forestry Program in Java, Indonesia

Abstract: Community forestry has been promoted as a strategy to tackle rural poverty in Indonesia. This article asks the extent to which the program can serve as a vehicle for poverty alleviation in the country. Based on the assessment on the economic outcomes of a community forestry scheme in the island of Java, this article concludes the scheme has yet to fulfill its high promises on providing forest users with genuine escape routes from their poverty-laden life. This paper further argues that instead of alleviating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 18 publications
1
14
1
Order By: Relevance
“…However, CFM does not guarantee the alleviation of poverty of forest-dependent communities. It has been set only to ensure the subsistence economy of the communities, and is yet to provide them with an escape from poverty in PHBM community forestry in Java (Maryudi and Krott 2012).…”
Section: Community Forest Management In Indonesiamentioning
confidence: 99%
“…However, CFM does not guarantee the alleviation of poverty of forest-dependent communities. It has been set only to ensure the subsistence economy of the communities, and is yet to provide them with an escape from poverty in PHBM community forestry in Java (Maryudi and Krott 2012).…”
Section: Community Forest Management In Indonesiamentioning
confidence: 99%
“…Moreover, the additional income from the Madiun model was modest and did not bridge the gap between the incomes of members and non-members (Table 11). As we have indicated, the benefits derivable from the Madiun model were negatively influenced by issues of quality, quantity, and continuity, as previously pointed out by Maryudi & Krott (2012) and Fujiwara et al (2012). Thus, within the current configuration, it is not possible for all members of the MPSDH to depend solely on the Madiun model for their livelihoods.…”
Section: Discussionmentioning
confidence: 70%
“…Few field surveys have analyzed the benefits for local people, e.g. household income surveys (Djamhuri 2012, Fujiwara et al 2012, Maryudi & Krott 2012. However, Mayers & Vermeulen (2002) demonstrated that concrete economic benefit "tended to be uppermost among the motives" for local people engaging in the Company-Community Forestry Partnerships; individual economic advantage is an important factor in the partnership's success.…”
Section: Introductionmentioning
confidence: 99%
“…Over one-tenth of the world's forests are estimated to be managed through community forestry arrangements (Maryudi and Krott 2012). Proponents of such arrangements emphasize that the ability to conserve forests depends critically on local people's involvement and active participation (Agrawal and Gibson 1999).…”
Section: Forest Energymentioning
confidence: 99%